Pemanfaatan Pekarangan Rumah untuk Budidaya Tanaman Olerikultura sebagai Upaya Pengurangan Biaya Konsumsi Rumah Tangga - Abdi Sakti Walenta; Toyib Toyib; Indah Suarni (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This study aims to evaluate the effectiveness of community service program (PKM) in utilizing household gardens for vegetable cultivation (olericulture) as an effort to reduce household consumption expenditure among women in Tendadongi Village, North Pamona District, Poso Regency. The program was implemented over five months involving 50 participants through a participatory learning approach combining theoretical training, direct practice, and continuous mentoring. Results demonstrated that 86% of participants successfully developed productive gardens with an average reduction in household consumption expenditure of 20–30% per month or IDR 150,000–250,000. Vegetable consumption frequency increased from 2–3 times to 4–5 times per week, reflecting significant improvement in family nutrition quality. The formation of an active productive garden community ensures program sustainability post-training. In conclusion, vegetable cultivation in household gardens is an effective strategy for strengthening household food security and reducing household food consumption burden.